Nutritional Management in a 101-Year-Old Woman with Physical Inactivity and General Weakness: A Case Report - Ryoko Mineyama; Fumie Tezuka; Nobuko Takagi; Shoichiro Kokabu; Masahiko Okubo (Geriatrics, 2023)
Japan has the world’s highest life longevity, and centenarian patients are no longer rare. However, sufficient information related to centenarians is not available. Herein, we report the case of a 101-year-old centenarian woman who recovered from extreme inactivity and general weakness, mainly through nutritional management at home, to understand instances of nutritional management in centenarians. The patient developed lethargy, with a rapid decline in activity levels and food intake. She was diagnosed with senility by a primary doctor. We concluded that she had no problems with feeding and swallowing and predicted that her motivation to eat had decreased. We planned an intervention that lasted three months. To reduce the risk of aspiration, we paid attention to her posture while eating. To stimulate her appetite, we increased the variety and color of food items. To consider both the texture of food and safety, we changed the form of foods from paste (IDDSI Level 4)-like to solid food of regular size as much as possible. We recommended that the patient consume her favorite sweet between meals to enjoy eating. Two and half months after the initial intervention, the patient’s inactivity and general weakness improved dramatically, which was recognized by her willingness to eat, laugh loudly, and hum, although she could not speak clearly. The patient finally was able to have dinner with her family.